Soil Moisture Determines Horizontal and Vertical Root Extension in the Perennial Grass Lolium perenne L. Growing in Karst Soil - Zhang, Jing; Wang, Jiamin; Chen, Jinyi; Song, Haiyan; Li, Suhui; Zhao, Yajie; Tao, Jianping; Liu, Jinchun (Frontiers in Plant Science, 2019)
Karst regions are characterized by shallow wide soil on hilly slopes and deep narrow soil in rocky trenches. To make full use of limited water and nutrients, plants have therefore developed a number of root extension strategies. This study investigated the effect of soil moisture on horizontal root extension in shallow wide soil and vertical root extension in deep narrow soil by assessing root growth responses, biomass allocation, and root distribution. A full two-way factorial blocked design of soil dimensions by water availability was followed. The perennial grass Lolium perenne L. was grown in shallow wide soil (SW) and deep narrow soil (DN) under high (W100%), moderate (W50%) and low (W30%) water availability, respectively. The main results were as follows: (1) The total biomass of L. perenne was not influenced either by soil habitat or by water application. Root length, root surface area, root biomass and root to shoot ratio all decreased with decreasing water application in SW, but not in DN. (2) With decreasing water application, the cumulative percentage of root length, root surface area and root biomass in 4 rings from the center out to 12 cm of SW showed a trend of W50% > W30% > W100% in SW, however, the cumulative percentage of root biomass in 4 layers from the surface to a depth of 36 cm was not significantly different between different water treatments. (3) Under all three water treatments, specific root length showed an increase but root length density showed a decreasing trend from the center outward in SW soil or from the surface to bottom in DN soil. Overall, these results suggest in shallow wide soil, soil moisture determines horizontal expansion of the roots in L. perenne, although the overall expansion ability was limited in severe drought. However, due to the relatively strong water retention ability, soil moisture changes were less obvious in deep narrow soil, resulting in no significant vertical extension of the root system. The root response of L. perenne helps our understanding of how herbaceous plants can adjust their belowground morphology to support their growth in harsh karst soil environments.